Rocket tracking using the second order integral fuzzy logic control - Iswanto Suwarno (Journal of Telecommunication Control and Intelligent System, 2021)
Fuzzy logic is logic with a degree of membership ranging from 0 to 1. Fuzzy logic is used to translate a linguistically expressed quantity. It is used as a control system because it is relatively simple and flexible to design and does not require complex mathematical models of the system to be controlled. The fuzzy control system keeps the rocket on track and moving at a constant speed. The fuzzy logic control system signal is used to control the rocket thrust. The Fuzzy Logic System has been selected as the controller because it works well on non-linear systems and simplifies program design. When used on systems that require rapid control, such as rockets, fuzzy logic systems do not perform optimally. Due to this issue, fuzzy logic is modified by incorporating second-order integral control into the modified fuzzy logic.